2016
DOI: 10.1158/1538-7445.am2016-3138
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3138: Changes in tumor cell-free DNA copy number instability (CNI) predict therapeutic response in metastatic cancers

Abstract: Background: Tumor cell-free DNA (cfDNA) has the potential to provide minimally invasive patient specific biomarkers to monitor tumor burden. Gains and losses of chromosomal regions - as a hallmark of cancer - have been detected in plasma as copy number aberrations (CNAs), and for several cancers a relation to tumor size has been reported. Longitudinal observations during anti-cancer therapy have been mostly anecdotal. We measured CNAs changes during treatment by computing a genomic copy number instability inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…If the measured CNI score does not decrease substantially, the chance of progression is over 90% in our validation group. We have seen similar effects for cytotoxic chemotherapy (24). These data justify prospective studies in specific cancer cohorts with defined approved treatment to validate the apparent universality of the CNI method for quantifying chromosomal instability.…”
Section: Discussionsupporting
confidence: 66%
“…If the measured CNI score does not decrease substantially, the chance of progression is over 90% in our validation group. We have seen similar effects for cytotoxic chemotherapy (24). These data justify prospective studies in specific cancer cohorts with defined approved treatment to validate the apparent universality of the CNI method for quantifying chromosomal instability.…”
Section: Discussionsupporting
confidence: 66%
“…To date, cfDNA derived CNA and CIN have been used to investigate response to treatment in in metastatic disease. For example, Weiss et al 32 showed that changes in cfDNA copy number instability (CNI) score could predict standard of care chemotherapy response in metastatic cancer. Here, we firstly assessed mCRC cfDNA samples for the ability to detect CNAs, and showed that CIN patterns from cfDNA reflected those from matched tumor samples, thus confirming the potential of plasma analysis for mCRC CIN subtyping.…”
Section: Discussionmentioning
confidence: 99%
“…To date, CNA and CIN have been used to investigate response to treatment in cfDNA in metastatic disease. Weiss et al 33 showed that changes in cfDNA copy number instability (CNI) score could predict therapeutic response in 24 metastatic cancer patients including mCRC. Overall, it was suggested that CIN changes might represent an early predictor of therapeutic response to standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%